Improving the mesodermal differentiation potential of human embryonic stem cells - Burridge, Paul Wesley (2008)
Human embryonic stem cells (hESCs) are thought to have enormous potential for use in regenerative medicine, whilst simultaneously allowing us insights into human embryonic development, disease modelling and drug discovery. Differentiation to mesodermal lineages, such as cardiomyocytes and blood, may allow for improved treatment of cardiac and haematopoietic diseases. hESC-derived immune cell types may also allow the circumnavigation of the immune barrier. This thesis aims to test the hypothesis that formation of hESC derivatives is regulated by the same mechanisms and ontology as in vivo embryo development. Therefore, by identifying and facilitating the mechanisms of mesoderm induction, hESC differentiation can be optimised to maximise the production of mesoderm, and, ultimately, mesoderm derivatives. Using a Xenopus laevis animal cap model with simultaneous treatment with activin B or fgf4, together with tall, Im02 and gatal mRNA, resulted in substantial increases in mesodermal, haemangioblast and erythropoietic cell markers. One of the most successful methods for hESC differentiation is by the formation of human embryoid bodies (hEBs). To reduce first the number of variables in current mass culture protocols for hEB formation, such as hEB size, a forced aggregation system was established that produced homogeneous hEBs from defined numbers of cells. This system was then optimised to enhance production beating cardiomyocytes by varying the number of hESCs used for hEB formation and also the number of days in culture. This system was assessed in four hESC lines and demonstrated substantial inter-line variability in cardiomyocyte production (1.6± 1.0% to 9.5±0.9°0). Differentiation was also performed using chemically defined media (CDM) with the addition of actiyin A and FGF2 and resulted in 23.6±3.6% of hESs producing beating cardiomyocytcs. In addition immunohistochemistry was performed to assess the relationship of cells expressing markers for mesoderm, pluripotency, ectoderm, and endoderm to establish a standard spatial and temporal map of hEB differentiation.